A theoretical framework to evaluate ICT disparities and digital divides: Challenges and implications for e-government development - Lněnička, Martin; Máchová, Renáta (de Gruyter Open, 2022)
Understanding and using ICT is critical for increasing effectiveness of the public sector, improving access to public services, enhancing transparency and engagement of various stakeholders in public decision-making processes. At the same time, utilization of new emerging technologies such as cloud computing, big data analytics, open data, social media, or Internet of Things has become more commonplace in recent years. This study aims to understand what determines ICT disparities and digital divides in the context of new technologies and digital world shifts. For this purpose, a theoretical framework of ICT-related indicators elucidating differences between the traditional and new approach is proposed. These ICT indicators were identified through the decomposition of related ICT and e-government indices together with explanatory factors derived from the literature. The European Union Member States were chosen as a sample for the exploratory analysis because of the availability of relevant indicators. More specifically, correlation, factor, regression, and cluster analyses were employed as empirical strategies to carry out this study. The Human Development Index together with research and development expenditure are the most important explanatory factors for the new approach, while the traditional set of indicators is still mostly correlated with the gross domestic product per capita. Finally, five clusters of Member States were identified and their implications for improving the use of ICT in the public sector are described.
Teoretický rámec pro hodnocení ICT nerovností a digitálních propastí: Výzvy a důsledky pro rozvoj e-governmentu
Keywords: cluster analysis; digital divide; e-government; European Union; exploratory factor analysis; ICT disparities; shluková analýza; digitální propast; e-government; Evropská unie; explorativní faktorová analýza; ICT nerovnosti